Replacement Surgery for Esophageal Atresia - Loukogeorgakis, Stavros P.; Pierro, Agostino (European Journal of Pediatric Surgery, 2013)
Esophageal replacement surgery is the treatment of choice in children with esophageal atresia (EA) when a long defect does not allow restoration of esophageal continuity, or when primary repair has failed. The stomach, colon, and small intestine have been used successfully to create conduits, but there is still no consensus among pediatric surgeons regarding the optimal method for substituting the native esophagus. Current evidence on short- and long-term outcomes of esophageal replacement originates from small-size, retrospective reports and well-designed comparative studies are lacking. Moreover, there is significant heterogeneity in the way outcomes are reported, which makes data pooling and comparison very challenging. In this review, we focus on the most recent evidence on outcomes of the most popular replacement techniques (colonic interposition, gastric transposition, gastric tube reconstruction, and jejunal interposition) used in pediatric patients with EA.
Keywords: esophageal atresia; esophageal replacement; colonic interposition; gastric transposition; gastric tube; jejunal interposition